Effects of donor funding on the HIV/TB programme outcomes in South Africa - Sokhela, Cleopatra Zinhle (University of the Witwatersrand, Johannesburg, 2021)
There has been decreasing donor funding for the past years, especially in developing countries. With the global economic crisis fuelled by the COVID-19 pandemic, there has been mounting pressure on governments and NGOs to sustain healthcare services and the HIV/TB programme implementation. Despite the efforts made in curbing HIV and TB in South Africa, the country is still struggling to meet its planned HIV and TB programme outcomes. The purpose of this study was to establish the factors that influence donor funding for HIV/TB programmes in South Africa and understand how NGOs utilise donor funds to achieve HIV/TB programme objectives. The study intended to determine the factors that influence donor funding for HIV/TB programme in South Africa; to establish how NGOs utilise donor funds to achieve HIV/TB programme objectives in South Africa; to establish strategies to sustain South African NGOs beyond donor funding, and to propose HIV/TB programme implementation strategies for NGOs in South Africa. The study was guided by the donor and recipient models intended to establish the relationship between donor interest, political interest, NGO funding, and HIV/TB programme outcomes and establish if NGOs sustainability is influenced by decreased donor funding. A quantitative and deductive study was conducted using an online survey. Data was collected from 308 respondents drawn from 30 donor-funded organisations across South Africa. The study's key findings revealed that donors give generously for the HIV/TB programme with no expected returns. Poor HIV/TB programme implementation by NGOs and lack of social impact affects future international funding opportunities. The study further established a positive relationship between recipient needs, NGO funding, and HIV/TB programme outcomes. The paper also concludes that NGO sustainability is not affected by declining donor funding, but a strong positive relationship between NGO leadership capacity and NGO sustainability was identified. A significant portion of respondents indicated that sustainability planning, government co-funding, diversified revenue-generating strategies, meaningful stakeholders' engagement and NGOs leadership capacity development were essential to ensure better HIV/TB programme outcomes and NGOs' sustainability beyond donor funding. In order to enhance the sustainability of donor-funded organisations and programme outputs, the study recommended the need for donors to review regulation governing donated funds utilisation; developing sustainability plan at the beginning of the funding cycle, NGOs to review their business models and NGO leadership capacity development on resource mobilisation and financial management. Future studies could focus on South African NGOs providing HIV/TB services readiness to transition from donor funding and evaluating the most effective revenue-generating strategies that NGOs can implement in South Africa
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Business Administration Johannesburg, 2021
Keywords: Donor interest; Donor funding; Recipient need; Sustainability; HIV/TB programme; Health outcomes; NGOs; UCTD; SDG-3: Good health and well-being